Monitoring Abundance and Distribution of Northern Gannets Morus bassanus in Western Iberian Waters in Autumn by Aerial Surveys - Araújo, Hélder (2022)
Several North Atlantic breeding seabirds, such as the Northern Gannet Morus bassanus, use Western Iberian Waters for wintering and migration. In this study, we aimed at producing absolute population estimates of post-breeding Gannets and evaluating the importance of the study area within the species’ migration range. We performed six aerial surveys in September and/or October each year between 2010 and 2015, covering 74,840km2 in total. Using line transect methodology, 3,672 Gannet sightings were recorded along 10,496.3 nautical miles (nm). Immature individuals and adults comprised approximately 87% of all sightings. Using Distance sampling, overall abundance was estimated at 89,930 birds, ranging from 58,010 individuals in 2014 to 128,140 in 2015. the highest densities per sector areas were recorded in the North and Centre sectors whereas the lowest densities were registered in the Galicia sector, the Spanish region within the study area. Gannets were mostly present in shallow shelf waters of the continental shelf, particularly between 3 and 20 nautical miles offshore. Habitat suitability models for Gannets in the study area were tested using several eco-geographical variables and chlorophyll concentrations were found to contribute most to explaining annual Gannet occurrence probabilities. A global interannual spatial analysis demonstrated the core areas for conservation of the Northern Gannet in Western Iberian Waters. Moreover, our results demonstrate that Western Iberian waters are used by almost 10% of the global Northern Gannet population, corroborating the existence of seabird hotspots during the non-breeding period, along migration corridors and at their wintering grounds.